O esquema semiótico subjacente à consecução de objetivos educacionais do domínio afetivo - Oliveira, Paulo Ricardo Sousa de (2023)
This work proposes to describe the semiotic scheme underlying the pedagogical proposal created by Bloom, Krathwohl and Masia (1974), in order to better explain the teacher's role in student engagement with learning. To illustrate the elements of the described scheme, the work Pedagogy of the Oppressed (1983) will be used. Bloom, Krathwohl and Masia propose a taxonomy of socio-affective objectives as a global scheme with connected tiers. With regard to discursive semiotics, the theory used as theoretical instrument for this research, it is considered, following Fontanille (2008), that current advances in the area account for the description of this object as a semiotic scheme which provides for the articulation of dimensions of action, cognition and passion integrated with the mobilization of value objects that enter the student's field of presence through the enunciative praxis of teaching-learning. For this endeavor, the semiotic concepts of tensivity, field of presence, semiotic scheme, modes of existence and enunciative praxis will be used. In this sense, the research results in the observation that not only are the three dimensions proposed by Fontanille present in the semiotic scheme of the object in question, but within it they find a particular arrangement that takes the following direction: affective objectives must be assumed or adhered to as specific affective dispositions by the student, but these dispositions need to be programmed by the teacher with a rationality of action that foresees stages in a journey. Finally, the affective dispositions experienced by the student must be the target of their own cognitive evaluation, through the comparison of the semiotic objects in their field of presence, otherwise the student runs the risk of becoming an excessively passionate subject and thus tends towards what may be semiotically characterized as fanaticism or naivety.